Peran Fear Of Missing Out, Review Beauty Influencer Terhadap Impulsive Buying Dan Kepuasan Pembelian (Studi Kasus Pada Produk Cushion Skintific Di Outlet Kendal) - Anggelia Eka Febiana; Bambang Sutedjo (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study was conducted to determine the effect of the role of fear of missing out (FOMO), beauty influencer reviews, on impulsive buying and purchase satisfaction. The population in this study were consumers of Skintific cushion products at the Kendal outlet. Quantitative methods were used in this study and data were measured using a Likert scale. Sampling used a purposive sampling method with sample criteria and a sample of 109 respondents was obtained. The results of this study indicate that the role of fear of missing out (FOMO) has a significant positive effect on impulsive buying. Beauty influencer reviews have a significant positive effect on impulsive buying. And impulsive buying also has a significant positive effect on purchase satisfaction.